2007
DOI: 10.2118/97803-pa
|View full text |Cite
|
Sign up to set email alerts
|

Novel Techniques for Measuring Heavy-Oil Fluid Properties

Abstract: Summary Investigating the properties of live heavy oil, as pressure declines from the original reservoir pressure to ambient pressure, can aid in interpreting and simulating the response of heavy-oil reservoirs undergoing primary production. Foamy oil has a distinctly different and more complex behavior compared to conventional oil as the reservoir pressure depletes and the gas leaves solution from the oil. Solution gas separates very slowly from the oil; thus, conventional pressure/volume/te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This implies that gas leaves solution all over the core, which was also previously measured in bulk liquid studies 15 . This is a function of the relatively small scale of these experiments; in longer core systems gas will only leave solution in the regions close to the production end of the core 16 .…”
Section: Secondary Waterfloodsupporting
confidence: 67%
“…This implies that gas leaves solution all over the core, which was also previously measured in bulk liquid studies 15 . This is a function of the relatively small scale of these experiments; in longer core systems gas will only leave solution in the regions close to the production end of the core 16 .…”
Section: Secondary Waterfloodsupporting
confidence: 67%
“…In previous work, however, it has been observed that oil AI can be related to the oil geometric mean relaxation time (16,17) since both vary monotonically with oil viscosity. Therefore, the de-convoluted oil average relaxation times were calculated and related to oil AI through the following empirical correlation (18) : where RHI = oil AI divided by water AI at the same temperature and T 2gm = geometric mean oil relaxation time. Figure 11 shows the NMR water and oil saturation predictions, plotted against the measured DS values obtained for sister samples.…”
Section: Oil Sands Characterizationmentioning
confidence: 99%
“…Some complementary means have been used to achieve more detailed information on the target fluid properties. CT scanning on long-core/sandpacked models has been utilized to determine the density field of the testing fluids contained in specialized holders. The density field scanning quality depends on the accuracy and frequency of the scanning. Microfluidic systems have been widely used in petroleum and chemical engineering, which offers a direct way of observation of phase behavior .…”
Section: Introductionmentioning
confidence: 99%